Multi-component shearography using optical fibre imaging-bundles - Groves, Roger M.; James, Stephen W.; Tatam, Ralph P. (International Society for Optical Engineering; 1999, 2003)
Shearography is a full-field non-contact optical technique usually used for the investigation of defects in nondestructive testing. In shearography interferometric speckle patterns recorded before and after object deformation are correlated, often by subtraction, to yield correlation fringes sensitive to displacement gradient, a parameter closely related to surface strain. Shearography is sensitive to the component of displacement gradient that is determined by the direction of the illumination and viewing directions, the optical wavelength and by the magnitude and direction of the applied shear. To perform a multi-component measurement requires illumination, or viewing, from a minimum of three directions, followed by a coordinate transformation to obtain the in-plane and out-of-plane displacement gradient components. This would normally require the use of either multiple optical sources or multiple interferometer heads and multiple cameras. In this paper the authors use a single laser source, a single interferometer head and camera, with four views of the object ported from the camera lenses to the interferometer using a four-leg optical fibre imaging bundle. This approach allows four components of displacement gradient to be recorded simultaneously. Experimental results from the multi-component shearography instrument are presented.